Exchange of a Single Amino Acid Residue in the HybG Chaperone Allows Maturation of All H2-Activating [NiFe]-Hydrogenases in Escherichia coli - Haase, Alexander; Sawers, R. Gary (Frontiers in Microbiology, 2022)
Biosynthesis of the NiFe(CN)2CO organometallic cofactor of NiFe-hydrogenase (Hyd) involves several discreet steps, including synthesis of the Fe(CN)2CO group on a HypD-HypC scaffold complex. HypC has an additional function in transferring the Fe(CN)2CO group to the apo-precursor of the Hyd catalytic subunit. Bacteria that synthesize more than one Hyd enzyme often have additional HypC-type chaperones specific for each precursor. The specificity determinants of this meanwhile large chaperone family are not understood. Escherichia coli synthesizes two HypC paralogues, HypC and HybG. HypC delivers the Fe(CN)2CO group to pre-HycE, the precursor of the H2-evolving Hyd-3 enzyme, while HybG transfers the group to pre-HybC of the H2-oxidizing Hyd-2 enzyme. We could show that a conserved histidine residue around amino acid position 50 in both HypC and HybG, when exchanged for an alanine, resulted in a severe reduction in activity of its cognate Hyd enzyme. This reduction in enzyme activity proved to be due to impaired ability of the chaperones to interact with HypD. Surprisingly, and only in the case of the HybGH52A variant, its co-synthesis with HypD improved its interaction with pre-HycE, resulting in maturation of Hyd-3. This study demonstrates that the conserved histidine residue helps enhance interaction of the chaperone with HypD, but additionally, and in E. coli only for HybG, acts as a determinant to prevent inadvertent maturation of the wrong large-subunit precursor. This study identifies a new level of control exerted by a bacterium synthesizing multiple NiFe-hydrogenases to ensure the correct enzyme is matured only under the appropriate physiological conditions.